Spatial heterogeneity of vegetation extent and the response to water level fluctuations and micro-topography in Poyang Lake, China. (May 2021) - Zheng, Lilin; Wang, Xiaolong; Li, Dahui; Xu, Guoyu; Guo, Yufei
Highlights: Vegetation expanded in lower elevation bands but deteriorated in higher bands. Vegetation in lower bands increased more significantly after Dam operation. High-flow events are destructive for vegetation in Dish-shaped Wetland. Low-flow events positively affected vegetation in other kinds of wetlands. Abstract: Wetland vegetation dynamics are vital but difficult to understand due to complex impact factors and their spatial heterogeneities. Poyang Lake, the largest freshwater lake in China, is well-known for its ecological importance as a floodplain wetland. However, heterogeneity in vegetation extent and its response to water regimes across different geomorphic units of Poyang Lake remain unclear to date. To address this gap, Landsat images acquired during dry seasons from 1987 to 2018 were selected to explore vegetation extent and its response to water level fluctuations across multiple elevation bands and four wetland types, namely Riparian Wetland (RW), Delta Wetland (DW), Dish-shaped Wetland (DSW), and Fan-shaped wetland (FSW). Results show that vegetation extent in lower elevation bands of the four wetland types increased remarkably with an average increase rate of 0.53 km 2 /year between 2003 and 2018 compared to −0.17 km 2 /year −1 during 1987 to 2002. Hydrological variables indicating high-flow events negatively affected vegetation extent in DSW while variables indicating low-flow events appear to be positive for vegetation extent in RW, DW, and FSW. Over-long floods as happened in 2016 has caused fatal damage to vegetation extent in DSW. In addition, extreme droughts in recent years caused by the Three Gorges Dam promoted significant (p < 0.05) vegetation expansion in lower elevation bands of RW, DW, and FSW, but a deterioration of vegetation extent in higher elevation bands, making Poyang Lake at risk of shrinkage and degradation. Human impacts on the evolution Poyang Lake system have caused wide concern, which also contribute to the proposal of Poyang Lake water control structure. Heterogeneity in vegetation extent and their response to water regimes across Poyang Lake provide precise spatial information for restoration efforts of the wetland ecosystem.